Contribution of smoking during pregnancy to inequalities in stillbirth and infant death in Scotland 1994-2003: retrospective population based study using hospital maternity records. (1st October 2009) - Gray, Ron; Bonellie, Sandra R; Chalmers, James; Greer, Ian; Jarvis, Stephen; Kurinczuk, Jennifer J; Williams, Claire
Abstract : Objective To quantify the contribution of smoking during pregnancy to social inequalities in stillbirth and infant death. Design Population based retrospective cohort study. Setting Scottish hospitals between 1994 and 2003. Participants Records of 529 317 singleton live births and 2699 stillbirths delivered at 24-44 weeks' gestation in Scotland from 1994 to 2003. Main outcome measures Rates of stillbirth and infant, neonatal, and post-neonatal death for each deprivation category (fifths of postcode sector Carstairs-Morris scores); contribution of smoking during pregnancy ("no, " "yes, " or "not known") in explaining social inequalities in these outcomes. Results The stillbirth rate increased from 3.8 per 1000 in the least deprived group to 5.9 per 1000 in the most deprived group. For infant deaths, the rate increased from 3.2 per 1000 in the least deprived group to 5.4 per 1000 in the most deprived group. Stillbirths were 56% more likely (odds ratio 1.56, 95% confidence interval 1.38 to 1.77) and infant deaths were 72% more likely (1.72, 1.50 to 1.97) in the most deprived compared with the least deprived category. Smoking during pregnancy accounted for 38% of the inequality in stillbirths and 31% of the inequality in infant deaths. Conclusions Both tackling smoking during pregnancy and reducing infants' exposure to tobacco smoke in the postnatal environment may help to reduce stillbirths and infant deaths overall and to reduce the socioeconomic inequalities in stillbirths and infant deaths perhaps by as much as 30-40%. However, action on smoking on its own is unlikely to be sufficient and other measures to improve the social circumstances, social support, and health of mothers and infants are needed.